Single European Railway Area and the Problem of Rail Infrastructure Charges - Case Studies in V4 Countries - Anna Dolinayová; Igor Dömény; Jan Jansák; Peter Šulko (Communications - Scientific letters of the University of Zilina, 2021)
This paper deals with the charging system and rail infrastructure fees use in V4 countries. The goal was to find out how the charges differ in terms of the train type, weight and distance traveled on different track categories. The charging principle for minimum access packages and for the access and services supplied in service facilities was investigated. Due to different technical, technological and other conditions for the rail infrastructure capacity utilization, the modeled situation was compared to the real one. This research shows differences between individual countries, both in the charging system and in the price for the rail infrastructure use (the prices were recalculated to € and in the PPP-purchasing power parity). It is interesting that the differences are not only significant with regard to the category of track used and the train’s weight (especially in the freight transport), but with regard to other factors, as well, in particular the type of train and price for the use of railway stations.